Sleep duration, sleep problems and developmental trajectories of urinary incontinence: a prospective cohort study. - Joinson, Carol; Grzeda, Mariusz T.; Heron, Jon; von Gontard, Alexander (European Child & Adolescent Psychiatry, 2024)
To examine if preschool sleep duration and sleep problems are associated with urinary incontinence (UI) at primary school-age. We used multinomial logistic regression to examine the association of child sleep duration/problems (3½ years) with UI trajectories (4–9 years) in 8751 (4507 boys, 4244 girls) from the Avon Longitudinal Study of Parents and Children. We adjusted for sex, socioeconomic indicators, mothers' emotional/practical/financial support, developmental delay, stressful life events, temperament, and emotional/behaviour problems. Preschool children who slept more than 8½ hours per night had a decreased probability of UI at school-age. There was a 33% reduction in odds of daytime wetting per additional hour of sleep (odds ratio [OR] = 0.67, 95% confidence interval [CI] 0.52–0.86). Sleep problems were associated with increased odds of UI e.g., getting up after being put to bed was associated with daytime wetting (OR = 2.20, 95% CI 1.43–3.39); breathing problems whilst sleeping were associated with delayed bladder control (OR = 1.68, 95% CI 1.12–2.52), and night-time waking was associated with persistent (day and night) wetting (OR = 1.53, 95% CI 1.16–2.00). Waking during the night and waking up early in the morning were associated with reduced odds of bedwetting at school-age (OR = 0.76, 95% CI 0.61–0.96 and OR = 0.80, 95% CI 0.64–0.99 respectively). Preschool children who sleep for longer have a lower likelihood of UI at school-age, whilst those with sleep problems are more likely to experience daytime wetting and combined (day and night) wetting, but not bedwetting alone. Short sleep duration and sleep problems in early childhood could be indicators of future problems attaining and maintaining bladder control.